2014
DOI: 10.1017/s0266462314000634
|View full text |Cite
|
Sign up to set email alerts
|

Is the Planned and Ongoing Project (Pop) Database a Suitable Tool to Reduce Duplication in the Process of Assessing New Health Technologies in the European Union? Preliminary Experience in the Context of the Eunethta Joint Action Project Framework (2010–2012)

Abstract: While the POP Database has the potential to reduce duplication of effort, this has not been realized during the 3-year period of the EUnetHTA Joint Action Project Framework, 2010-12. Further evidence needs to be gathered to determine whether the POP Database is effective and whether the benefits outweigh the resources required to maintain it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The rate of similar or identical projects has continuously been around ten percent since the start of JA1 [7]. A thorough evaluation of the usage of the database at the end of JA1 [8] reported that 75% of the replying partners considered the POP Database a useful tool for sharing knowledge, experience and information. 42% indicated that the POP database provided an important first-hand overview of ongoing HTA activities at a European level as well as an easy access to other agencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of similar or identical projects has continuously been around ten percent since the start of JA1 [7]. A thorough evaluation of the usage of the database at the end of JA1 [8] reported that 75% of the replying partners considered the POP Database a useful tool for sharing knowledge, experience and information. 42% indicated that the POP database provided an important first-hand overview of ongoing HTA activities at a European level as well as an easy access to other agencies.…”
Section: Resultsmentioning
confidence: 99%
“…A direct reduction of duplication in conducting HTAs was reported twice. Collaborative activities usually focus on information exchange of literature search protocols, extraction tables, information on the description and the technical characteristics of the technology as well as the health problem, executive summaries and full project reports [8].…”
Section: Resultsmentioning
confidence: 99%